Beveridge Report (Pictorial charts with explanatory notes) - Beveridge, William Henry Beveridge, Baron, 1879-1963. Social insurance and allied services
1943-01 1943 1940s 14 pages : illustrations 10 Chart 5. FAMILY ALLOWANCES AND INCOMES. Relation between income and size of families in York 1936. Size of families. Under 53s. 53s. to 59s.11d. 60s. to 69s.11d. 70s. and over. Average of those earning 53s. and over. 0 children 14.7 23.0 26.4 34.3 29.1 1 child 22.0 31.3 34.2 28.1 30.8 2 children 26.4 18.2 21.1 26.1 22.6 3 children 15.6 8.9 9.7 6.2 7.8 4 or more 21.3 18.6 8.6 5.3 9.7 100 100 100 100 100 (Poverty and Progress. B. Seebohm Rowntree). Chart 6. INDUSTRIAL ASSURANCE. Total Population 1938. 47,600,000 (estimate, Statistical Year Book of the League of Nations, 1939/40) Policies continuing to maturity 1937/9. 103,000,000 (Beveridge Report. Appendix D). Total Policies issued 1937/9. Total Policies issued about 10 million. Policies continuing to maturity about 33% Policies allowed to lapse nearly 40% Made free of further contributions for reduced sums over 14% Surrendered for cash before maturity over 113% (Beveridge Report. Appendix D and G. D. H. Cole: Beveridge Explained.) Costliness of Administration. The bars representing premium income of Industrial Assurance Companies, and contributions to Beveridge Plan have been made the same length in order to show the percentage cost of administration under both. Actual Figures are:- Industrial Assurance Premium Income 1937/40 £72,995,000 Expenses of Management £23,809,000 Beveridge Plan. (Social Insurance). Total Expenditure £553,000,000 Cost of Administration £18,000,000 The February issue will deal with Italy. 126/TG/377/1/1/153